Question
upstudy study bank question image url

Solve the following system of equations. \[ \begin{aligned}-4 x+y & =13 \\ 5 x+y & =-14\end{aligned} \]

Ask by Brewer Barnett. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the system is \( x = -3 \) and \( y = 1 \).

Solution

We are given the system of equations:   -4x + y = 13   5x + y = -14 One simple method is to eliminate y by subtracting the first equation from the second. Step 1: Subtract the first equation from the second:   (5x + y) – (–4x + y) = -14 – 13 Simplify the left side:   5x + y + 4x - y = 9x Simplify the right side:   -14 - 13 = -27 So, we have:   9x = -27 Step 2: Solve for x:   x = -27 / 9   x = -3 Step 3: Substitute x = -3 back into any of the original equations to find y. Using the first equation:   -4(-3) + y = 13   12 + y = 13   y = 13 - 12   y = 1 Thus, the solution to the system is:   x = -3, y = 1.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the given system of equations: 1. Start with the two equations: \[ \begin{aligned} -4x + y & = 13 \quad \text{(1)} \\ 5x + y & = -14 \quad \text{(2)} \end{aligned} \] 2. We can eliminate \(y\) by subtracting equation (1) from equation (2). This gives us: \[ (5x + y) - (-4x + y) = -14 - 13 \] Simplifying this, we get: \[ 5x + y + 4x - y = -27 \implies 9x = -27 \] 3. Now, solve for \(x\): \[ x = -3 \] 4. Substitute \(x = -3\) back into either original equation to find \(y\). We'll use equation (1): \[ -4(-3) + y = 13 \] \[ 12 + y = 13 \implies y = 1 \] 5. Thus, the solution to the system of equations is: \[ x = -3, \quad y = 1 \] The solution can be expressed as the ordered pair: \[ (-3, 1) \]

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy